(untitled) (International Seven Journal of Multidisciplinary, 2023)
This study looked at the Sustainable Development Goals (SDGs) as an implementation of actions and study proposals for improving the quality of life on the planet. The qualitative method was used, with bibliographical and exploratory research on various databases such as Scielo and Google Scholar. The Sustainable Development Goals (SDGs) find fertile ground for aspirations and practices that can leverage the construction of a society committed to social transformation. The implementation of the SDGs in schools will enable, among other actions, an increase in affirmative inclusion policies for socially vulnerable people, as well as innovating in the development of the Pedagogical Political Projects of school units and helping to build didactic, pedagogical and structuring guidelines in the educational sphere. However, there are many challenges to the implementation of the SDGs in countries, such as the lack of financial resources and the absence of targets to meet. Faced with the current globalized scenario, it is necessary to understand that development is not just about economic growth and technological innovation. It’s not just today that we face various situations such as poverty, lack of health care, education, security, as well as issues of racial and gender discrimination. However, even with so much global progress, these worrying issues are becoming more visible. It is therefore essential that the 2030 Agenda becomes a reality.